Cortical thickness, local gyrification index and fractal dimensionality in people with acute and recovered Anorexia Nervosa and in people with Bulimia Nervosa. (30th May 2020) - Cascino, Giammarco; Canna, Antonietta; Monteleone, Alessio Maria; Russo, Andrea Gerardo; Prinster, Anna; Aiello, Marco; Esposito, Fabrizio; Salle, Francesco Di; Monteleone, Palmiero
Highlights: Cortical thinning seems to be state-dependent in patients with Anorexia Nervosa. Gyrification index alterations disappear in recovered patients with Anorexia Nervosa. Higher values of cortical thickness are present in patients with Bulimia Nervosa. Alterations of local gyrification index are present in patients with Bulimia Nervosa. No alterations of Fractal Dimensionality detected in eating disorders. Abstract: Eating disorders (EDs) have a possible neurodevelopmental pathogenesis. Our study aim was to assess regional cortical thickness (CT), local gyrification index (lGI) and fractal dimensionality (FD), as specific markers of cortical neurodevelopment in ED females. Twenty-two women with acute anorexia nervosa (acuAN), 10 with recovered anorexia nervosa (recAN), 24 with bulimia nervosa (BN) and 35 female healthy controls (HC) underwent a 3T MRI scan. All data were processed by FreeSurfer. Compared to recAN group women with acuAN showed a lower CT in multiple areas, while compared to HC they showed lower CT in temporal regions. BN group showed higher CT values in temporal and paracentral areas compared to HC. In multiple cortical areas, AcuAN group showed greater values of lGI compared to recAN group and lower values of lGI compared to HC. The BN group showed lower lGI in left medial orbitofrontal cortex compared to HC. No significant differences were found in FD among the groups. Present results provide evidence of CT and lGI alterations in patients with AN and, for the first time, in those with BN. Although these alterations could be state-dependent phenomena, they may underlie psychopathological aspects of EDs.